Butyric acid – a well-known molecule revisited - Katarzyna Borycka-Kiciak; Tomasz Banasiewicz; Grażyna Rydzewska (Gastroenterology Review)
The properties of butyric acid, and the role it plays in the gastrointestinal tract, have been known for many years. However, the newest research shows that butyric acid still remains a molecule with a potential that has not as yet been fully exploited. The article provides an outline of relevant up-to-date knowledge about butyric acid, and presents the expert position on the clinical benefits of using butyric acid products in the therapy of gastrointestinal diseases.